Duration of oral contraceptive use and the risk of venous thromboembolism. A case-control study. Issue 141 (May 2016) - Martinelli, Ida; Maino, Alberto; Abbattista, Maria; Bucciarelli, Paolo; Passamonti, Serena M.; Artoni, Andrea; Gianniello, Francesca; Peyvandi, Flora
Abstract: Introduction: Oral contraceptive (OC) use increases the risk of venous thromboembolism (VTE), but the effect of duration of use remains to be elucidated. Patients and methods: This case-control study was aimed to investigate the duration of OC use on the risk of VTE according to women age, periods of use, prevalence of other risk factors and the role of thrombophilia abnormalities. Seven-hundred patients and 209 controls who used OC were stratified into short users (≤ 1 year), long users (1 to 5 years), and very long users (> 5 years). Results and conclusions: Compared to non-users, the odds ratio (OR) for VTE was 9.0 (95% CI 6.9–12.2) in short, 6.5 (95% CI 4.8–83.7) in long and 5.9 (95% CI 4.4–8.1) in very long users. The risk of VTE in short users was highest in women ≤ 30 years and in the first year of use (OR 13.1, 95% CI 7.7–22.4) and decreased afterward (OR 7.7, 95% CI 5.0–11.9). This trend was not observed in women > 30 years. Compared to non-carriers and non-users, a joint effect of thrombophilia abnormalities and OC use on VTE risk was observed particularly in short users (OR 62.2, 95% CI 29.8–129.6), but also afterward (OR 25.4, 95% CI 16.5–39.2). Other transient risk factors for VTE were present in 25% of very long and 16% of short users. In conclusion, the risk of VTE in OC users decreases over time only before 30 years and in first users. Thrombophilia abnormalities strongly interact with the duration of OC use in determining VTE. Highlights: Risk of VTE in OC users decreases over time only before 30 years and in first users. Thrombophilia and the duration of OC use strongly interact in determining VTE. The longer the use of OC the higher the number of transient risk factors at VTE.